2000
DOI: 10.1007/s12043-000-0044-y
|View full text |Cite
|
Sign up to set email alerts
|

Density oscillations in laser produced plasma decelerated by external magnetic field

Abstract: This paper presents the dynamics as well as the stability of laser produced plasma expanding across the magnetic field. Observation of some high frequency fluctuations superimposed on ion saturation current along with structuring in the pin hole images of x-ray emitting plasma plume indicate the presence of instability in the plasma. Two type of slope in the variation of x-ray emission with laser intensity in the absence and presence of magnetic field shows appearance of different threshold intensity of laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…21,22 The average energy of laser produced ion at I = 10 8 Wcm −2 is in the range of KeV. Torrisi et al 23 reported average energy of laser produced charge state 1 + are increased ranging from 18% to 161% in the presence of external magnetic field.…”
Section: A Ion Energy and Dose Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 The average energy of laser produced ion at I = 10 8 Wcm −2 is in the range of KeV. Torrisi et al 23 reported average energy of laser produced charge state 1 + are increased ranging from 18% to 161% in the presence of external magnetic field.…”
Section: A Ion Energy and Dose Measurementsmentioning
confidence: 99%
“…As a result plume confinement occurs. 28 There is extensive collision of plasma species because of confinement of plasma through the magnetic field. As a result more plasma constituents are formed in the confinement region.…”
Section: A Ion Energy and Dose Measurementsmentioning
confidence: 99%
“…A saturation in the x-ray emission was also noticed in the form of change in the slope with an increase in the laser intensity. However this saturation was found to be correlated with the loss of plasma energy in form of the generation of an instability and high energy particles in the plasma along with emission of high energy x-rays (Rai et al, 2000a, Rai et al, 2000b.…”
Section: Laser Absorption and Shielding Effect In Plasmamentioning
confidence: 99%